Atividades e regimes de autorregulação: atributos de integridade e os efeitos na tutela de interesses difusos - Albuquerque, Juliana Nakata (2020)
This study introduces a conceptual presentation of self-regulation, both with respect to its activities, and with reference to instituted regimes, by examining the reasons associated with the rise of the entities and the factors that drive their growth and adherence. Then, from the understanding of the characteristic elements of private control regimes, the activities and structures of prominent international self-regulatory entities, which cover systems in several countries, were analyzed. Regimes in operation in Brazil were further indicated. Based on this knowledge as well as on the references of the activities and systems, the necessary elements for the validity and integrity of the entities were appointed. Procedural and structural requirements, which bases the exercise of authority for the pursued change of behavior or to achieve objectives and their nature, were also indicated. Those analyses were performed in order to verify the possible breadth of interests and the consequences of private regulatory regimes. Finally, several types of relationship with public authorities were examined, in view of the increasing endorsement to the regimes and even some anxiety for the delegation of regulatory activities to private systems. It is also referred the safeguards required by different governments and major international authorities on the topic